Injury data from the first six seasons (2006-2012) of the FIS injury surveillance system in world cup alpine skiing - Steenstrup, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
FIS established in collaboration with the Oslo Sports Trauma Research Center (OSTRC) a continuous injury reporting system for all FIS events, the FIS Injury Surveillance System (ISS), prior to the 2006/07-season. The objective of the FIS ISS is to provide data on injury trends in international skiing and snowboarding at the elite level with the long-term goal of reducing injury risk. During the 2006/07-season, Flørenes et al. (2011) investigated in a methodological study which method would produce the most complete and accurate record of injuries to World Cup (WC) skiers. They found that retrospective interviews with athletes/coaches gave the most complete picture of injuries in this setting. Therefore, retrospective interviews are conducted by physicians or physiotherapists from the OSTRC at the WC finals at the end of each winter season. All athletes who are present in person are interviewed, while coaches or medical staff are interviewed if the athlete is not present (due to injury or for other reasons). Athletes, coaches and medical staff are asked to recall any acute injury requiring medical attention, occurring in training or competition during the WC season. Injury reporting from the first six (2006-12) seasons of the FIS ISS showed that the risk of injury among WC alpine skiers was even higher than expected. The most frequently injured body part was the knee, and over 50% of these knee injuries were severe (Flørenes et al. 2009). Bere et al. (2014) reported that men had a higher rate of injury than women. These sex differences were even more pronounced during WC races. However, there was no sex difference in the risk of knee or ACL injuries (Bere et al. 2014). The injury rate was highest in downhill (17.2 injuries per 1000 runs), followed by super-G (11.0), giant slalom (9.2) and slalom (4.9) (Flørenes et al. 2009). Based on the high injury rates and severity of these injuries, FIS initiated several steps to improve athlete safety in the following seasons. ABSTRACT FROM AUTHOR